Access to novel fluorovinylidene ligands via exploitation of outer-sphere electrophilic fluorination: new insights into C–F bond formation and activation. Issue 4 (24th December 2015) - Milner, Lucy M.; Hall, Lewis M.; Pridmore, Natalie E.; Skeats, Matthew K.; Whitwood, Adrian C.; Lynam, Jason M.; Slattery, John M.
Abstract : Metal fluorovinylidene complexes have been synthesised for the first time by direct electrophilic fluorination of metal alkynyls. Abstract : Metal vinylidene complexes are widely encountered, or postulated, as intermediates in a range of important metal-mediated transformations of alkynes. However, fluorovinylidene complexes have rarely been described and their reactivity is largely unexplored. By making use of the novel outer-sphere electrophilic fluorination (OSEF) strategy we have developed a rapid, robust and convenient method for the preparation of fluorovinylidene and trifluoromethylvinylidene ruthenium complexes from non-fluorinated alkynes. Spectroscopic investigations (NMR and UV/Vis), coupled with TD-DFT studies, show that fluorine incorporation results in significant changes to the electronic structure of the vinylidene ligand. The reactivity of fluorovinylidene complexes shows many similarities to non-fluorinated analogues, but also some interesting differences, including a propensity to undergo unexpected C–F bond cleavage reactions. Heating fluorovinylidene complex [Ru(η 5 -C5 H5 )(PPh3 )2 (CCFR)][BF4 ] led to C–H activation of a PPh3 ligand to form an orthometallated fluorovinylphosphonium ligand. Reaction with pyridine led to nucleophilic attack at the metal-bound carbon atom of the vinylidene to form a vinyl pyridinium species, which undergoes both C–H and C–F activation to give a novel pyridylidene complex. Addition of water, in the presence of chloride, leads to anti-Markovnikov hydration of a fluorovinylidene complex to form an α-fluoroaldehyde, which slowly rearranges to its acyl fluoride isomer. Therefore, fluorovinylidenes ligands may be viewed as synthetic equivalents of 1-fluoroalkynes providing access to reactivity not possible by other routes.